Therapeutic advances in medical oncology (Sage, 2009)
"The journal will publish well-designed original research results of systemic cancer treatments including chemotherapy, endocrine therapy, biological therapy and immunotherapy. ... We will also specialise in publishing drug reviews of clinical relevancy. Thus, the journal will provide medical oncologists with a much-needed resource for cancer drug treatments."